Handling efforts criminal act illegal logging by KPHL Ampang in perspective criminologi and victimologi - Iqbal, Muhammad; Subardan, Ismak (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2018)
Rampant illegal logging is a nutural problem by a very dangerous country, because of illegal logging crimes can affect all aspect including exstra ordinary crime others thus providing a very close relationship. In this research the author has a long term goal against long term research about illegal logging in KPHL Ampang area which will provide a solution so it can be a way out in carrying out an act of prevention or prosecution against illegal logging. As for the specific targets to be achieved in this study is looking for criminal causality illegal logging in the ampang area, looking for efforts to handle illegal logging crime by KPHL Ampang in the perspective of criminologi and victimology, and look for factors that hamper law enforcement illegal logging in KPHL Ampang. To achieve all goals both general and special the autor uses normative and emprical research methods where normative research explains the rules wheras empirical reserch look for data related to causality the pattern of law enforcement implementation on illegal logging crime. Furthermore in this research will give result to become new guidance and method of KPHL ampang in preventing the occurrence of illegal logging and can be used to be more broadly at the government level as awhole in the district of sumbawa.Key word: Ampang, criminal act, illegal logging, crimonologi and victimology